Perceived Meaning on McDonalds’ Happy Meal® Promotional Videos by Blue and White Collar Workers in Surabaya - Valerie Febrina Anggara (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
This study observes the perceived meanings of McDonalds’ Happy Meal®promotional videos produced by two different social classes of workers, which are White and Blue Collar workers as respondents. After finding out what the perceived meanings are from the respondents, writer proceeds on to the analyzing process in order to find out the differences between White and Blue Collar respondents’ perceived meanings. The study uses descriptive qualitative approach to explain the meaning of qualitative material in a more systematic way. The writer concludes that white collar respondents tend to prioritize pride, prestige and esteem. Meanwhile, blue collar respondents tend to prioritize their primary needs and responsibilities before spending on secondary needs.